Astragaloside IV alleviates oxidative stress‑related damage via inhibiting NLRP3 inflammasome in a MAPK signaling dependent pathway in human lens epithelial cells. Issue 4 (6th March 2022) - Xiao, Xili; Zheng, Yanlin; Mo, Ya; Wang, Wanjie; Li, Xiang; Wang, Juan
Abstract: Oxidative stress alters cellular microenvironment, facilitating cell apoptosis and inflammatory response, and oxidation of lens constituents may ultimately result in cataracts. Astragaloside IV (AS‐IV) exhibits a variety of pharmacological activities, such as antioxidative and anti‐inflammatory activity via regulating various signaling pathways. However, the effect of AS‐IV on lens epithelial cells and its potential therapeutic role in cataracts remained to be investigated. In this study, AS‐IV prevented H2 O2 ‐induced injury and inflammatory response in human lens epithelial cell line HLE‐B3 through inhibiting NLRP3 inflammasome in a mitogen‐activated protein kinase‐dependent pathway, providing a potential novel therapeutic strategy for cataracts.